Statistics for business and economics - Anderson, David R. (David Ray), 1941-; Sweeney, Dennis J.; Williams, Thomas A. (Thomas Arthur), 1944- (Mason, Ohio : South-Western Cengage Learning, 2014)
Statistics for Business and Economics, 11e introduces sound statistical methodology within a strong applications setting. The authors clearly demonstrate how statistical results provide insights into business decisions and present solutions to contemporary business problems. New cases and more than 350 real business examples and memorable exercises, 150 of which are new in this edition, present the latest statistical data and business information. --from publisher description
Contains a website access card.
Includes bibliographical references (p. [976]-977) and index.
Keywords: Commercial statistics -- Methodology; Economics -- Statistical methods; Statistics